2009
DOI: 10.1007/s00240-009-0182-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of specific α-1A/1D blocker on lower urinary tract symptoms due to double-J stent: a prospectively randomized study

Abstract: The aim of our study was to evaluate the effect of tamsulosin in improving symptoms in patients with indwelling double-J ureteral stents. This prospective study lasted from April 2006 to March 2008. All the patients with symptomatic lower ureteral stones with <15 mm diameter were enrolled, and were prospectively randomized (random numbers table) into two groups. A total of 154 patients, with insertion of a double-J ureteral stent after ureteroscopic stone removal. In group 1, 75 patients were enrolled and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 24 publications
4
98
0
Order By: Relevance
“…In terms of the results of statistical analysis, significant differences in IPSS voiding symptom sub-scores (MD, -2.66; 95% CI, -4.36 to -0.96) were detected; however, no significant differences in IPSS storage symptom sub-scores (MD, -0.93; 95% CI, -2.28 to 0.43) were detected (Table IV). The pooled USSQ urinary symptoms score data (MD, -5.84; 95% CI, -9.35 to-2.33) for seven studies (13,16,(22)(23)(24)(25)30) demonstrated that α 1 -blockers administration significantly reduced USS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of the results of statistical analysis, significant differences in IPSS voiding symptom sub-scores (MD, -2.66; 95% CI, -4.36 to -0.96) were detected; however, no significant differences in IPSS storage symptom sub-scores (MD, -0.93; 95% CI, -2.28 to 0.43) were detected (Table IV). The pooled USSQ urinary symptoms score data (MD, -5.84; 95% CI, -9.35 to-2.33) for seven studies (13,16,(22)(23)(24)(25)30) demonstrated that α 1 -blockers administration significantly reduced USS.…”
Section: Resultsmentioning
confidence: 99%
“…A Russian article published in Urologiia met the inclusion criteria according to the English abstract in PubMed; however it was subsequently excluded, since the full text could not be located (21). A total of 14 RCTs including 1,075 patients were included in the present meta-analysis (13,15,16,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations